Syria the fall of the house of Assad - Lesch, David W. (Yale University Press, 2012)
This book explores Bashar al-Assad's failed leadership, his transformation from bearer of hope to reactionary tyrant, and his regime's violent response to the uprising of his people in the wake of the Arab Spring. Lesch charts Assad's turn toward repression and the inexorable steps toward the violence of 2011 and 2012